COVID-19-related hyperglycemia is associated with infection of hepatocytes and stimulation of gluconeogenesis - Barreto, Ester A; Cruz, Amanda S; Veras, Flavio P; Martins, Ronaldo; Bernardelli, Rafaella S; Paiva, Isadora M; Lima, Thais M; Singh, Youvika; Guimarães, Raphael C; Damasceno, Samara; Pereira, Nayara; Alves, João Manoel; et al. (Proceedings of the National Academy of Sciences - PNAS, 2023)
Occurrence of hyperglycemia upon infection is associated with worse clinical outcome in COVID-19 patients. However, it is still unknown whether SARS-CoV-2 directly triggers hyperglycemia. Herein, we interrogated whether and how SARS-CoV-2 causes hyperglycemia by infecting hepatocytes and increasing glucose production. We performed a retrospective cohort study including patients that were admitted at a hospital with suspicion of COVID-19. Clinical and laboratory data were collected from the chart records and daily blood glucose values were analyzed to test the hypothesis on whether COVID-19 was independently associated with hyperglycemia. Blood glucose was collected from a subgroup of nondiabetic patients to assess pancreatic hormones. liver biopsies were collected to assess the presence of SARS-CoV-2 and its transporters in hepatocytes. In human hepatocytes, we studied the mechanistic bases of SARS-CoV-2 entrance and its gluconeogenic effect. SARS-CoV-2 infection was independently associated with hyperglycemia, regardless of diabetic history and beta cell function. We detected replicating viruses in human hepatocytes from liver biopsies and in primary hepatocytes. We found that SARS-CoV-2 variants infected human hepatocytes in vitro with different susceptibility. SARS-CoV-2 infection in hepatocytes yields the release of new infectious viral particles, though not causing cell damage. We showed that infected hepatocytes increase glucose production and this is associated with induction of PEPCK activity. Furthermore, our results demonstrate that SARS-CoV-2 entry in hepatocytes occurs partially through ACE2- and GRP78-dependent mechanisms. SARS-CoV-2 infects and replicates in hepatocytes and exerts a PEPCK-dependent gluconeogenic effect in these cells that potentially is a key cause of hyperglycemia in infected patients.